Financial Management Strategy To Maximize Profits In The Digital Era For Young Entrepreneurs In Palu City - Marwana; Dasa febriyant; Annisa nurfaidah (Yayasan Amerta Insan Unggul, 2025)
In the digital era, effective financial management plays a crucial role in ensuring the sustainability and profitability of young entrepreneurs, particularly in Palu City. This study aims to analyze financial management strategies that utilize digital technology to optimize business performance and maximize profits. Using a qualitative approach supported by interviews, observations, and document analysis of 50 young entrepreneurs, this research explores how financial technology applications, data analytics, and digital marketing are integrated into business operations. The findings reveal that 80% of respondents use cloud-based accounting systems such as Xero and QuickBooks to manage financial records efficiently, while 70% adopt digital payment platforms like OVO, GoPay, and Dana to improve transaction speed and reduce risks. Furthermore, 85% of young entrepreneurs using social media marketing reported a significant increase in sales. The study emphasizes that implementing financial technology, effective budgeting, reserve fund planning, and compliance with digital financial regulations are key to improving profitability and ensuring business continuity. However, continuous innovation and adaptation to emerging technologies remain essential for long-term success. This research contributes to the understanding of digital-based financial management strategies that support entrepreneurship development in local economies, particularly in post-disaster regions such as Palu City.